(untitled) (Hackensack, N.J., 2006)
The exploration of the subnuclear world is carried out through increasingly complex experiments covering a wide range of energies and in a large variety of environments - from particle accelerators and underground detectors to satellites and space laboratories. For these research programs to succeed, novel techniques, new materials and new instrumentation need to be used in detectors, often on a large scale. This book reviews the advances made in all technological aspects of the experiments at various stages.
Keywords: Nuclear astrophysics,Nuclear physics,Vật lý hạt nhân,Particle acceleration,Nuclear counters,Particles (Nuclear physics),Medical physics,Vật lý y tế,Vật lý không gian hạt nhân; Instruments,Thiết bị,Insturments,Thiết bị